Influence of calcination temperature towards Fe-TiO2 for visible-driven photocatalyst - Ibrahim, Siti Aida; Ahmid, Muhamad Nazim (Trans Tech Publications, 2017)
TiO2 is one of the most promising photocatalysts that is widely used for environmental clean-up due to its ability to degrade organic pollutants in air or water. The purpose of this research is to enhance the photocatalytic activity of TiO2 by absorbing energy in visible light region in order to degrade pollutants. In this study, the nanostructured Fe-TiO2 was successfully synthesised via a combined method of sol-gel and calcination process. The calcination temperatures used varied from 400°C to 800 °C. The as-prepared samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and UV-Vis spectroscopy (UV-Vis). XRD results show that the phases of TiO2 are dependent on calcination temperature. It is found that both TiO2 and Fe-TiO2 phases were transformed from anatase to rutile as the temperatures were increased. FESEM images revealed that the particle size was agglomerated and the average grain size was about 54 nm to 66 nm. UV-Vis analysis indicated that the incorporation of Fe and varied calcination temperature may affect the optical properties as the absorption profile was shifted from 445 nm to 585 nm. Thus, the results show that Fe-TiO2 is a highly potential photocatalyst to degrade pollutants under visible light irradiation.